2022
DOI: 10.1037/apl0000872
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with new members: Team members’ reactions to newcomer’s attractiveness and sex.

Abstract: We examine how team members respond to the inclusion of new members' physical attractiveness and sex. Drawing on Social Exchange Theory, we argue and show that incumbent team members engage in three behaviors (mimicry, ingratiation, and challenging) in response to the inclusion of more or less attractive male or female members in their team. Using a multilevel experimental design, we show that existing team members mimic newcomers who are higher on physical attractiveness and that the effect is more pronounced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…Research on the dynamics of hierarchy has focused on how rank is acquired (and lost), the mutability of hierarchy due to the widespread desire for rank (e.g, Bendersky & Pai, 2018), as well as how organizational members can increase their relational influence (Bourgoin et al, 2020). Specific to the process of integrating new members, researchers have tended to focus on hierarchy competition dynamics (e.g., Min et al, 2021; Rink & Ellemers, 2015). Our findings build upon these perspectives by showing how organizational members strategically shape hierarchical relations to be flatter in some situations with the goal of promoting the agency of lower ranking members (e.g., during debriefing periods) and advancing communal goals (e.g., socializing), while enforcing rank differences in others (e.g., to promote efficient communication in the operation control center).…”
Section: Discussionmentioning
confidence: 99%
“…Research on the dynamics of hierarchy has focused on how rank is acquired (and lost), the mutability of hierarchy due to the widespread desire for rank (e.g, Bendersky & Pai, 2018), as well as how organizational members can increase their relational influence (Bourgoin et al, 2020). Specific to the process of integrating new members, researchers have tended to focus on hierarchy competition dynamics (e.g., Min et al, 2021; Rink & Ellemers, 2015). Our findings build upon these perspectives by showing how organizational members strategically shape hierarchical relations to be flatter in some situations with the goal of promoting the agency of lower ranking members (e.g., during debriefing periods) and advancing communal goals (e.g., socializing), while enforcing rank differences in others (e.g., to promote efficient communication in the operation control center).…”
Section: Discussionmentioning
confidence: 99%
“…Though we found that the amount and distribution of informal hierarchy strength in our student teams to be similar to those in non-student teams, contextual factors that are more prevalent in non-student teams may impact informal hierarchy strength changes. For example, the student sample minimized confounds that may impact informal hierarchy strength such as the presence of a formal team leader (Oedzes et al, 2019) or fluid membership (Bunderson, Van der Vegt, & Sparrowe, 2014; Min et al, 2020). Examining such contextual factors may provide additional insights into informal hierarchy strength changes.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers could also relate team familiarity to the evolution of teamwork (Yong et al, 2021) and study whether team familiarity moderates uncertainty when team composition changes (Jin et al, 2017), for example when new members join (Min et al, 2021), when robots join the team (Savela et al, 2021) or in fast-paced work contexts, where teams need to unlearn existing knowledge that has become obsolete in order to stay relevant (Kim & Park, 2021). Moreover, uncertainty reduction theory (Berger, 1988) could be utilized to investigate how team familiarity influences uncertainty when new members join a team and when team context changes (e.g.…”
Section: Advancing the Theoretical Underpinnings Of Team Familiarity ...mentioning
confidence: 99%